Sex-based differences in growth-related IGF1 signaling in response to PAPP-A2 deficiency: comparative effects of rhGH, rhIGF1 and rhPAPP-A2 treatments - María del Mar Fernández-Arjona; Juan Antonio Navarro; Antonio Jesús López-Gambero; Marialuisa de Ceglia; Miguel Rodríguez; Leticia Rubio; Fernando Rodríguez de Fonseca; Vicente Barrios; Julie A. Chowen; Jesús Argente; Patricia Rivera; Juan Suárez (Biology of Sex Differences, 2024)
Abstract Background Children with pregnancy-associated plasma protein-A2 (PAPP-A2) mutations resulting in low levels of bioactive insulin-like growth factor-1 (IGF1) and progressive postnatal growth retardation have improved growth velocity and height following recombinant human (rh)IGF1 treatment. The present study aimed to evaluate whether Pappa2 deficiency and pharmacological manipulation of GH/IGF1 system are associated with sex-specific differences in growth-related signaling pathways. Methods Plasma, hypothalamus, pituitary gland and liver of Pappa2 ko/ko mice of both sexes, showing reduced skeletal growth, and liver of these mice treated with rhGH, rhIGF1 and rhPAPP-A2 from postnatal day (PND) 5 to PND35 were analyzed. Results Reduced body and femur length of Pappa2 ko/ko mice was associated with increases in: (1) components of IGF1 ternary complexes (IGF1, IGFBP5/Igfbp5, Igfbp3, Igfals) in plasma, hypothalamus and/or liver; and (2) key signaling regulators (phosphorylated PI3K, AKT, mTOR, GSK3β, ERK1/2 and AMPKα) in hypothalamus, pituitary gland and/or liver, with Pappa2 ko/ko females having a more prominent effect. Compared to rhGH and rhIGF1, rhPAPP-A2 specifically induced: (1) increased body and femur length, and reduced plasma total IGF1 and IGFBP5 concentrations in Pappa2 ko/ko females; and (2) increased Igf1 and Igf1r levels and decreased Ghr, Igfbp3 and Igfals levels in the liver of Pappa2 ko/ko females. These changes were accompanied by lower phospho-STAT5, phospho-AKT and phospho-ERK2 levels and higher phospho-AMPK levels in the liver of Pappa2 ko/ko females. Conclusions Sex-specific differences in IGF1 system and signaling pathways are associated with Pappa2 deficiency, pointing to rhPAPP-A2 as a promising drug to alleviate postnatal growth retardation underlying low IGF1 bioavailability in a female-specific manner.